Opowieść o genezie i przemianach kwartalnika literacko-artystycznego "Fraza". Przypisy do historii czasopism literacko-artystycznych "przełomu" = The story of the genesis and transformation of the literary and artistic quarterly "Fraza". - Rabizo-Birek, Magdalena (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
Published in Rzeszów, the quarterly "Fraza" is one of the remaining literary and artistic magazines which were created during the period of political transformation after 1989. They were usually created by young writers and critics connected with local universities or cultural institutions, based in peripheral cities, without significant cultural traditions. In the great majority they were created by a generation born after 1960. The author of the article, the editor-in-chief of "Fraza" from 1998, presents the genesis, specificity of non-institutional functioning and the nature of the periodical. This article presents the changes occurring in the magazines in the last 30 years, caused by the transformation of the cultural model (dominance of popular culture and progressive marginalization of high culture): an IT revolution that helped editorial and publishing work, but also successively destroyed the paper forms of magazines. The author draws attention to the instability of the state's cultural policy towards cultural periodicals, both at the central and local levels, which causes problems in their financing and speeds up the decision to close them down. Presenting many details from the history of "Fraza" and other turn-of-the century periodicals, she tries to take into account various circumstances and factors that shaped them, including the specificity and dynamics of literary life, the stage of the existence of magazines (young, mature and aging) and the influence of editorial individuals on contents, programs and forms of their activity. The author presents the achievements of these magazines, significant for literature after 1989, but pessimistically assumes their impending demise.
Keywords: czasopisma literacko-artystyczne; czasopisma polskie; kwartalnik Fraza; historia; literary and artistic magazines; Polish magazines; Fraza quarterly; history